Effect of Employees' Values on Employee Satisfaction in Japanese Retail and Service Industries. (1st January 2019) - Matsuki, Tomonori; Nakamura, Jun
Abstract : The Japanese workforce has decreased rapidly over the past few decades, and this is expected to continue. Retail and service industries are already experiencing human-resource shortages. In these industries, nonregular employees feature prominently. For most companies, recruitment is difficult, and employees change jobs often, making securing staff an important business issue. Nonregular and regular employees are treated differently; the problem is thus partly social in nature. However, some nonregular employees are content, although their work conditions are not good. Here, text mining was used to explore differences between the values of regular and nonregular employees in the retail and service industries.